z_(1)+z_(2)=1-2*i+(4-2*i)=1-2*i+4-2*i=[b]5-4*i[/b]
2)
z_(1)-z_(2)=1-2*i-(4-2*i)=1-2*i-4+2*i=[b]-3[/b]
3)
z_(1)*z_(2)=(1-2*i)*(4-2*i)=1*4-2*i*4+1*2*i+(2i)^2=
(так как i^2=-1)
=4-8*i+2*i+4*(-1)=0-6*i=[b]=-6*i[/b]
4)
[m]\frac {z_{1}}{z_{2}}=\frac{ 1-2\cdot i}{4-2 \cdot i}=[/m]
( умножаем и числитель и знаменатель на (4+2*i)
[m]=\frac{( 1-2\cdot i)(4+2 \cdot i)}{(4-2 \cdot i)(4+2 \cdot i)}=[/m]
применяем формулу разности квадратов в знаменателе
[m]=\frac{( 1-2\cdot i)(4+2 \cdot i)}{(4)^2-(2i)^2}=\frac{4-8\cdot i+3\cdot i+4}{16+4}[/m]
[m]=\frac{8-5\cdot i}{20}=\frac{8}{20}-\frac{5}{20}\cdot i[/m]